Electron-induced dynamics of small molecules of atmospheric and astrochemical relevance - Heathcote, D (2020)
Electron ionisation, and electron scattering in general, is a fundamental physical process. Ubiquitous in the known universe, the interaction of electrons with molecules is thus of great interest.